Transvaginal Repair Using Acellular Collagen Biomesh for the Treatment of Anterior Prolapse - Citgez, Sinharib; Demirkesen, Oktay; Ozdemir, Fatih; Gevher, Fethullah; Demirdag, Cetin; Onal, Bulent; Cetinel, Bulent (Urology Journal, 2014)
Purpose: To determine the results and satisfaction of the patients underwent transvaginal repair of cystocele in our clinic. Materials and Methods: From January 2006 to October 2010, 15 patients with a mean age of 64 years (ranged 47-85 years) underwent transvaginal cystocele repair using acellular collagen biomesh. The patients were presented with vaginal mass in 10, dyspareunia and urge incontinence in 5 while 4 of them had both stress and urge incontinence. Grade 4 cystocele was determined in 2 patients, grade 3 in 9 and grade 2 in 4. Concomitant transobturator tape (TOT) was performed in 4 patients. Patient satisfactions were determined after the operation. Results: The mean follow-up time was 23.5 (12-60) months. There was no postoperative complication in early follow- up period. Cystocele was recurrent in 1 patient. The success rate was 93.4%. Urinary incontinence was continued in 1 patient after TOT. Nearly all of the patients (14/15) were satisfied from the operation. Conclusion: Transvaginal cystocele repair with using acellular collagen biomesh appears to be a safe and effective method. Further prospective and randomized controlled studies including large series of patients are needed.